Stimulation of fungi originated from Wamena Biological Garden on maturity of compost nutrient and the number of phosphate solubilizing and nitrogen fixing microbes - SRI WIDAWATI (Society for Indonesian Biodiversity, 2005)
The aims of the research was to know ability of fungi catalisator, i.e. Aspergillus niger, Trichoderma viridae, and Chaetomium sp. to increase composting process and decrease C/N ratio content. The experiments used grass as carbon source, cow dung as nitrogen source, and A. niger, T. viridae, and Chaetomium sp. as catalisator. The result showed that the activators accelerated the compost maturity process. The compost was contained phosphate solubilizing fungi (± 109 cell/g), phosphate solubilizing bacteria (± 109 cell/g), and nitrogen fixing bacteria (± 108 cell/g). The C/N ratio of compost was 8.90. Key words: activator fungi, compost, phosphate solubilizing microbes, nitrogen fixing, bacteria, Wamena Biological Garden.